THE CONFLICT OF BEATRICE PRIOR IN ROTHâ€™S DIVERGENT - Gusti Ayu Made Rai Suarniti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2018)
This writing focused on â€œThe Conflict of Beatrice Prior in Rothâ€™s Divergentâ€. The specific aim of this scientific writing is to find out and describe the conflicts that are faced by Beatrice Prior and also to find out the source of the conflicts in Rothâ€™s Divergent. The data of the research were taken from Divergent written by Veronica Roth. The research method used in this study are qualitative â€“descriptive method. The data were collected through library research, then the data were analyzed using non-formal technique. The theory of literature is important in analyzing character while the theory of psychology is used in analyzing conflict. The theory of character is taken from Lajos Egri about Three dimensions of characterization, while theory of conflict is taken from Tayla Bauer and Berrin Endargon. Based on the result of analysis, it can be concluded that The Conflict of Beatrice Prior in Rothâ€™s Divergent consists of internal conflict and external conflict. Beatrice Prior or known as Tris is the main character of this story based on the role of the character in the story. The types of Trisâ€™s internal conflicts are categorized as Intrapersonal conflict. Meanwhile, the types of Trisâ€™s external conflicts are categorized as Interpersonal conflict and Intergroup conflict. The source of the conflicts are differing in Attitudes, Values, and Perceptions.